STRATEGIES OF EDUCATIONAL INSTITUTIONS IN BUILDING LEARNING INDEPENDENCE OF CHILDREN WITH DISABILITY - Daulay, Annisa Arrumaisyah; Saputra, Randi; Walidaini, Birrul (Nurul Jadid University, 2022)
This research discusses the learning independence of physically disabled students. This research was conducted at SMA Negeri 1 Ulu Moro’o. The informants consist of classroom teachers and parents of the students. The purpose of this study is to obtain an overview of the learning independence physically disabled students and the obstacles experienced by these students themselves and teachers. The research method used is a descriptive method with a qualitative approach. This research method is used because it has the purpose of describing the situation of the problem objectively under natural conditions. The data collection techniques used are observations and interviews. In general, the results of this study illustrate that students can be independent in learning only in limited learning or activities that use physical so that it needs attention and help from an educator.